Tunable thermal expansion in zinc-bonded composites: Zn/Si/Zn0.75Sn0.2Mn0.05NMn3. (1st March 2020) - Wang, Z.C.; Lin, J.C.; Tong, P.; Kong, M.G.; Zhang, X.K.; Yang, C.; Song, W.H.; Sun, Y.P.
Abstract: Negative thermal expansion (NTE) materials can compensate for the coefficient of thermal expansion (CTE) of normal metals. Currently, it is challenging to prepare NTE/metal composites facing the practical demands. We report the tunable CTEs between –0.39 and 6.19 ppm/K around room temperature in Zn/Si/Zn0.75 Sn0.2 Mn0.05 NMn3 composites. The low-melting Zn acts as the adhesive, while Zn0.75 Sn0.2 Mn0.05 NMn3 is the CTE compensator. Moreover, the composites have high compression strength (225 MPa) and thermal conductivity (52 W/K m), showing great potentials as electronic thermal management materials. Our results suggest an effective way to realize low-CTE composites with excellent performance based on NTE compounds. Graphical abstract: Image, graphical abstract